2009
DOI: 10.1016/j.mar.2009.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Performance measurement design within its organisational context—Evidence from China

Abstract: a b s t r a c tThis paper presents an action research study that looks at the design of a performance measurement system in a large Chinese state-owned enterprise, focussing on how change happens. A stakeholder analytical framework is developed to bridge the gaps in westerndeveloped models when they are applied in a Chinese context. Analysis revealed the factors determining the nature of change and shaping the performance measurement system. Political constraints and the unavailability of key databases act as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 46 publications
5
46
0
2
Order By: Relevance
“…For instance, Hopper et al (2001) and Wickramasinghe and Hopper (2005) both found that management controls in Sri Lanka and Bangladesh were captured by the political parties in power and their sponsored trade union parties, and that they, rather than human resources managers, determined workers' pay, leave and promotions. Similar patterns, such as political considerations in rational measures of performance measurement, budgeting and operational decision making, are also evident in the Chinese public sector (Li & Tang, 2009).…”
Section: Rational Accounting Framework and Context: Mismatched Realitiesmentioning
confidence: 67%
“…For instance, Hopper et al (2001) and Wickramasinghe and Hopper (2005) both found that management controls in Sri Lanka and Bangladesh were captured by the political parties in power and their sponsored trade union parties, and that they, rather than human resources managers, determined workers' pay, leave and promotions. Similar patterns, such as political considerations in rational measures of performance measurement, budgeting and operational decision making, are also evident in the Chinese public sector (Li & Tang, 2009).…”
Section: Rational Accounting Framework and Context: Mismatched Realitiesmentioning
confidence: 67%
“…SPMS promotes organizational learning through the functions of communications, dialogues, discussions and evaluations of the business strategic topics among the members of an organization. The positive effects of SPMS on the alignment of management processes with business strategy or business strategic objectives were empirically demonstrated in prior research (e.g., Ittner et al, 2003;Chenhall, 2005;Li and Tang, 2009). However, their research mostly focused on the strategic alignment itself, and did not clearly uncover and confirm the learning facilitating roles of SPMS.…”
Section: Effect On It Infrastructure For Kmmentioning
confidence: 74%
“…SPMS, which combines financial, strategic (e.g., customers and innovations) and business processes or operating measures, is a useful tool to gauge how well a firm meets its strategic targets. Because of this combination or integration characteristic of SPMS, SPMS can enhance the understanding of the cause-effect linkages between operations and business strategy and goals, and between various aspects of the value chain including suppliers and customers (Li and Tang, 2009). SPMS, which focuses on integrating business operations or functional processes with business strategy, is defined as a system that translates competitive strategy into deliverable results and reveals ways to achieve business strategic objectives.…”
Section: ⅱ Theoretical Underpinnings and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations